Adaptive LADRC Parameter Optimization in Magnetic Levitation - Qinghua Ouyang; Kuangang Fan; Yahui Liu; Na Li (IEEE Access, 2021)
In this study, an adaptive linear active disturbance rejection control is proposed to achieve steady levitation of the magnetic levitation ball. The proposed algorithm was designed and its convergence was proven via derivation. It can address the difficulty in parameter tuning of the controller and realize the real-time self-adaptive optimization of parameters. Besides, to verify the effectiveness of the proposed parameter tuning strategy, we analysed the anti-interference ability and tracking effects of SMC, LADRC and A-LADRC in different cases. Finally, the results showed that the anti-interference ability of A-LADRC is stronger than SMC and LADRC. In addition, the anti-interference effect intensifies when the interference increases. The designed controller also performs the best tracking performance among these three controllers. Therefore, A-LADRC exhibits better robustness and dynamic performance.